Transformative Influence of Online Marketing on the Growth and Success of Small and Medium-Scale Enterprises in Anambra State, Nigeria - Ekwunife Gabriel Okafor; Njelita Chukwudi (New Advances in Business, Management and Economics Vol. 1, 2025)
The use of social media for marketing has grown to be an important practice for businesses that wish to take advantage of the opportunities created by the changes in the digital world, the growing connectivity of people online and the growth in the use of mobile phones. Through the use of social media, companies can improve their competitive edge in areas such as the share of the market, increased sales growth, customers’ patronage and retention, the development of brand loyalty, and even more outreach. This work, therefore, looks at how the use of online marketing affects the performance of small and medium enterprises in Anambra State with more emphasis on social media marketing as the factor or process responsible for customer satisfaction, customer loyalty, and market share in the business enterprise achieving marketing goals. Particularly this is applicable in a case study where survey research was employed. Specifically, 50,213 employees and operators working in the Anambra state-registered small and medium enterprises (SMEs) which were 2233 in number were sampled (SMEDAN, 2021). Using a 95 percent confidence level and the Taro Yamane sampling formula, the appropriate sample size came to 397 respondents. The information was collected by the use of structured questionnaires that were later analyzed with the aid of descriptive statistics and simple regression using SPSS software. The findings reveal that social media marketing has a considerable effect on market share, customer satisfaction, and even customer loyalty. Consequently, the study recommends that SMEs develop strategic social media marketing plans and allocate adequate resources to maximize the benefits of digital engagement.